The role of palmitoylation and transmembrane domain in sorting of transmembrane adaptor proteins - Chum, Tomáš; Glatzová, Daniela; Kvíčalová, Zuzana; Malínský, Jan; Brdička, Tomáš; Cebecauer, Marek (Journal of cell science, 2016)
Plasma membrane proteins synthesised at the endoplasmic reticulum are delivered to the cell surface via sorting pathways. Hydrophobic mismatch theory based on the length of the transmembrane domain (TMD) dominates discussion about determinants required for protein sorting to the plasma membrane. Transmembrane adaptor proteins (TRAP) are involved in signalling events which take place at the plasma membrane. Members of this protein family have TMDs of varying length. We were interested in whether palmitoylation or other motifs contribute to the effective sorting of TRAP proteins. We found that palmitoylation is essential for some, but not all, TRAP proteins independent of their TMD length. We also provide evidence that palmitoylation and proximal sequences can modulate sorting of artificial proteins with TMDs of suboptimal length. Our observations point to a unique character of each TMD defined by its primary amino acid sequence and its impact on membrane protein localisation. We conclude that, in addition to the TMD length, secondary sorting determinants such as palmitoylation or flanking sequences have evolved for the localisation of membrane proteins.
Keywords: Jurkat Cells; LAT; Adaptor Proteins, Signal Transducing; lipoylace; HEK293 buňky; Protein Structure, Tertiary; Structure-Activity Relationship; terciární struktura proteinů; PAG; Jurkat buňky; membránové proteiny; Membrane Proteins; HEK293 Cells; HeLa buňky; vztahy mezi strukturou a aktivitou; Palmitoylation; Cell Membrane; extracelulární prostor; lidé; Extracellular Space; HeLa Cells; Humans; buněčná membrána; adaptorové proteiny signální transdukční; Protein sorting; Protein Transport; Lipoylation; glykosylace; Glycosylation; transport proteinů; Plasma membrane; Transmembrane domain